Manajemen Kepala Madrasah terhadap Pembelajaran Bahasa Arab untuk Meningkatkan Mutu Lulusan Siswa di MAN Tanjungpinang Provinsi Kepulauan Riau - Satrio; Martinis Yamin; Fadlilah (PT. PENERBIT TIGA MUTIARA, 2024)
This paper analyzes the application of madrasah principal management to Arabic language learning in improving the quality of student graduates at MAN Tanjungpinang. This research method is a qualitative field research method that is carried out holistically. The approach used is phenomenology. The results of this study are to improve the quality of student graduates at MAN Tanjungpinang, Riau Islands through Arabic language learning, then it can use madrasah principal management, namely through; a) planning, b) organizing, c) implementing, and e) supervising. Planning includes needs analysis, short and long term goals, and relevant curriculum development. Organizing by setting a clear organizational structure with specific assignments and responsibilities for each Arabic language teaching staff. Implementation by actively implementing an innovative Arabic language curriculum, ensuring that Arabic language learning materials are always up-to-date and relevant to student needs. Supervision by conducting periodic monitoring of the Arabic language learning process to ensure that the curriculum and teaching methods are implemented according to plan.